Comparing high-end and low-end early adopters of battery electric vehicles. (June 2016) - Hardman, Scott; Shiu, Eric; Steinberger-Wilckens, Robert
Highlights: This paper presents a sample of 340 adopters of battery electric vehicles (BEVs). Two groups of BEV adopters are identified; these are high-end and low-end adopters. These adopters have significantly different socio-economic and psychographic profiles. These groups also have significantly different perceptions of their vehicles, with high-end adopters have superior opinions. Finally high-end adopters are more likely to continue with BEV ownership than low-end adopters. Abstract: Battery electric vehicle adoption research has been on going for two decades. The majority of data gathered thus far is taken from studies that sample members of the general population and not actual adopters of the vehicles. This paper presents findings from a study involving 340 adopters of battery electric vehicles. The data is used to corroborate some existing assumptions made about early adopters. The contribution of this paper, however, is the distinction between two groups of adopters. These are high-end adopters and low-end adopters. It is found that each group has a different socio-economic profile and there are also some psychographic differences. Further they have different opinions of their vehicles with high-end adopters viewing their vehicles more preferentially. The future purchase intentions of each group are explored and it is found that high-end adopters are more likely to continue with ownership of battery electric vehicles in subsequent purchases. Finally reasons for this are explored by comparing each adopter group's opinions of their vehicles to their future purchase intentions. From this is it suggested that time to refuel and range for low-end battery electric vehicles should be improved in order to increase chances of drivers continuing with BEV ownership.